Tariqa-Based Education Management to Improve The Character of Students (Case Study at Pesantren Al Jauhari Garut and Pesantren At-Tadzkir Majalengka) - Witrin Noorjutstiatini; Achmad Sanusi; Iim Wasliman; Hendi Suhendraya Muchtar (Ridwan Institute, 2022)
This study aims to describe, analyze and produce a hypothetical model of tarekat-based education management to improve the character of students. The research procedure used is a qualitative approach with a case study design. Data collection techniques were carried out by (1) Observation, (2) Interview and (3) Documentation. The results showed that (1) Tarekat- based education preparation in an effort to improve the character of students was quite effective, (2) Tarekat-based education in Islamic boarding schools was effective. (3) The character values of the santri (students) embodied in the Tareqa boarding school have been sufficiently realized, (4) The process of implementing tarekat-based education in the Islamic Boarding School has been quite maximal, (5) The most important problem faced in the implementation of Tarekat-based education is the pattern of student behavior that sometimes difficult to regulate, (6) The solution to the problems faced in the implementation of tarekat- based education is effective enough to overcome the problems of tareqa-based education. planning and organizing matters. Prior to the implementation, the boarding school has prepared human resources such as a teaching board that is committed to the implementation of tarekat- based education